Single limb dynamics of jumping turns in dogs. (November 2021) - Söhnel, Katja; Andrada, Emanuel; de Lussanet, Marc H.E.; Wagner, Heiko; Fischer, Martin S.; Rode, Christian
Abstract: Maneuverability is of paramount importance for many animals, e.g., in predator-prey interactions. Despite this fact, quadrupedal limb behavior in complicated maneuvers like simultaneous jumping and turning are not well studied. Twenty adult sport Border Collies were recorded while jumping over an obstacle and simultaneously turning. Kinetic and kinematic data were captured in synchrony using eight force plates and sixteen infrared cameras. These dogs were familiar with the task through regular participation in the dog sport agility. The experiments revealed that during landing, higher lateral forces acting in the forelimbs compared to hindlimbs. During landing, the outer limbs produced about twice the inner limbs' force in both vertical and lateral directions, showing their dominant contribution to turning. Advanced dogs showed significantly higher lateral impulse and stronger inner-outer limb asymmetry regarding lateral impulses than beginner dogs, leading to significantly stronger turning for advanced dogs. Somewhat unexpected, skill effects rarely explained global limb dynamics, indicating that landing a turn jump is a constrained motion. Constrained motions leave little space for individual techniques suggesting that the results can be generalized to quadrupedal turn jumps in other animals. Highlights: Jumping turns is a superposition of jumping and turning. High lateral forces and impulses are exerted in the outer limbs. strongest turning around the vertical axis is achieved during the landing of the forelimbs. Advanced dogs reach stronger turning due to higher lateral forces and stronger inner-outer limb asymmetry.